Application of the fast multipole boundary element method to underwater acoustic scattering. - Wilkes, D; Duncan, Alexander (Engineers Media Pty Ltd., 2011)
A numerical model is being developed in the MATLAB programming environment to model the acoustic field scattered from a submarine hull. Due to the acoustic impedance properties of water, small particle velocities yield large acoustic pressures, resulting in coupled fluid-structure interactions. Numerical methods can be employed to calculate the scattered acoustic field for complex geometries. Traditionally, these techniques required both significant memory and computational time, limiting their usefulness. Recently, the fast multipole algorithm (FMA) has been used to efficiently calculate the acoustic field on an object's surface, while the finite element method was used to model the object's interior. The pressure hull of a submarine can be represented as a piecewise continuous isotropic elastic solid, thus the FMA can also model the submarine interior, with the unknowns expressed on each surface. A possible method for coupling an exterior acoustic model to a structural model, both calculated via the FMA, is outlined here. Some initial acoustic fast multipole boundary element method results are presented.